The use of a thromboelastogram (TEG®) protocol to decrease the usage of blood products in adult patients undergoing cardiac surgery at Universitas Academic Hospital, Bloemfontein, Free State, South Africa - MogorosI, J. B. (University of the Free State, 2020)
Background: Blood transfusion during cardiac surgery carries potential complications like transfusion reactions, increased length of hospital stays and financial costs1-4. Efforts through research of Point of Care (POC) strategies like the Thromboelastogram (TEG®) that provide health care practitioners with rapid, predictive and outcome based POC coagulation testing algorithms5,6 to guide perioperative blood transfusions are underway. Objectives: There is currently no POC protocol to guide blood product use at Universitas Academic Hospital in Bloemfontein, South Africa. Aim: The primary aim of the study was to establish whether the use of a TEG® protocol versus physician decision will reduce blood product usage in adult patients undergoing elective cardiac surgery at Universitas Academic Hospital in Bloemfontein, Free State, RSA. Methods: A comparative, descriptive study using: A. The physician decision group consisting of a retrospective file review of the usual clinical practice, using clinical notes from Meditech® (an integrated software system that provides solutions to healthcare organisations throughout Africa) and the National Health Laboratory System (NHLS) Lab Trak® (an inter-systems results portal), 25 June to 30 September 2019, and B. The TEG® protocol group consisting of a prospective cohort of patients using the usual clinical practice with the addition of TEG®-based protocol, 25 June to September 2020. Results: The COVID pandemic markedly reduced elective theatre lists owing to the small prospective study population. Average cell saver volume (276ml, p < 0.0001) and FFP (2 units, p = 0.05) were statistically significant. There was no statistical significance in the average volume of RCC (1 unit, p = 0.6679), Platelets (1 unit, p = 0.2329) or Cryoprecipitate (1 unit, p = 0.6382) saved between the two groups. Conclusion: Cell saved blood and FFP transfusion were statistically and clinically significantly reduced in the TEG® protocol group. While red blood cell, platelet, cryoprecipitate, and total blood product transfusion had reduced trends in the TEG® protocol group though not of statistical significance. We suggest that this preliminary report be considered for future MMed or PhD research because it was a first in our institution and there is great potential to improve patient outcomes and contribute to best practice regarding patient blood management in the perioperative period.
Keywords: Dissertation (M.Med (Anaesthesiology))--University of the Free State, 2020; Thromboelastogram; Rotational thromboelastometry; Point of care; Cardiac surgery; Cardiopulmonary bypass; Coagulation